(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
The diamondback moth (DBM), Plutella xylostella (L.) (Lepidoptera: Plutellidae) is one of the most serious cosmopolitan pests of cruciferous plants. It causes severe damage to crop quality and production, with estimated global losses of 20-40% per year. Consumer preference regarding pest-free and uncontaminated crop, unavailability of highly competitive natural enemies as well as migratory nature of DBM has obligated for the mandatory use of insecticides. The over reliance and indiscriminate use of chemical insecticides to control DBM has lead to development of resistance against almost all the modern insecticides. In addition, it has also developed resistance against most of the Bt strain. To overcome the problem of resistance, there is an urgent need for new and highly efficient method to control DBM which must be eco-friendly, cost effective and has minimum impact on the environment. One of such alternatives is nanotechnology which fulfil all the criteria to become an ideal insecticide or delivery system for insect pest management especially DBM. Nanotechnology offers great improvement in the field of pesticides as it is less toxic, shelf-life enhancement and higher water solubility. Loading of Indoxacarb on nanoparticles are reported to be highly effective they suppressed the activity of detoxification enzymes such as GST, CarE, and P450. Green synthesis of AgNPs, Single walled carbon nano tube (SWCNT) also exhibits larvicidal and pupicidal effect. These are also reported to adversely affect food consumption, growth, pupation and fecundity of P. xylostella.These nanoparticles have been found to be more stable, also the controlled release of active ingredient for a long time and provides target specific control of P. xylostella for solving adverse situations ofthe crop fields like less food security, lesser food productivity and environmental imbalance.